Lithium from breast‐milk inhibits thyroid iodine uptake and hormone production, which are remedied by maternal iodine supplementation. (4th February 2021) - Ahmed, Irfan; Ma, Victor; Liu, Yuanchao; Khan, Muhammad Shehzad; Liu, Zhenhui; Zhang, Chi; Paidi, Santosh Kumar; Manno, Francis A. M.; Amjad, Noreen; Manno, Sinai H. C.; Ahmed, Rafay; Law, Alan W. L.; et al.
Abstract: Background: Lithium is especially taken as a maintenance medication for Bipolar Disorder. In women with bipolar disorder, lithium is often effective during postpartum period, but breast‐feeding for medicated mothers is controversial because of harmful effects for her child. At present, the biological mechanisms of lithium are not well‐understood, affecting its usage and overall health implications. Procedure: We developed a rat lithium and breast‐feeding model at human therapeutic levels to study the effects of lithium exposure through breast‐milk on pups' thyroid function. Novel laser analytical spectroscopy, along with traditional blood and immunohistochemical tests, were applied to further investigate the mechanisms behind the thyroid dysfunction. Maternal iodine supplementation was evaluated as a therapeutic method to address the pups' thyroid dysfunction. Results: Pups exposed to lithium via breastmilk, even with the dam on a sub‐therapeutic level, experienced weight gain, reduced blood thyroxine (T4 ), and elevated blood urea nitrogen, indicating effects on thyroid and kidney function. We show that lithium inhibited iodine uptake by thyroid follicles, initiating a mechanism that reduced iodination of tyrosine, thyroglobulin cleavage, and thyroid hormone production. Importantly, infant thyroid function can be significantly improved by administering supplementary iodine to the medicated dam's diet during breast‐feeding. Conclusion: These results elucidate the mechanisms of lithium in thyroid function, provide valuable information on use postpartum, and suggest a clinically applicable remedy to side‐effects. The results are particularly important for patients (and their infants) who respond well to lithium and need, or choose, to breast‐feed.